Evaluasi Teknologi Pendukung Work-From-Home: Studi Kasus pada Badan Kepegawaian Negara - Avianto, Galih Kenang (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
Changes have not followed the application of working-from-home (WFH) in government agencies in the regulations that cover it. As a result, government investment and efforts to encourage the adoption of WFH to increase employee productivity are not optimal due to various factors. Factors influencing employees to adopt WFH technology need to be analyzed so that employees are willing to do WFH post-pandemic and its implementation can support organizational goals. UTAUT is the basis for developing a research model by adding other factors based on literature studies. PLS-SEM was used to analyze 102 respondents' data and test the eight hypotheses proposed. Three of the eight hypotheses were statistically proven. Perceived self-efficacy and Compatibility factors positively affected WFH adoption with a predictive power of 57.7% of the model. The Adoption factor positively affects Use with the model's predictive power of 47.9%. Organizations implementing WFH must provide training and identify types of work suitable to be applied remotely so that employees will continue to carry out WFH even though the pandemic has ended.